TREE SPECIES DIVERSITY IN A PRISTINE MONTANE FOREST PREVIOUSLY UNTOUCHED BY HUMAN ACTIVITIES IN FOJA MOUNTAINS, PAPUA, INDONESIA - Asep Sadili; Kuswata Kartawinata; Herwasono Soedjito; Edy Nasriadi Sambas (BRIN Publishing (Penerbit BRIN), 2018)
ADILI, A., KARTAWINATA, K., SOEDJITO, H. & SAMBAS, E. N. 2018. Tree species diversity in a pristine montane forest previously untouched by human activities in Foja Mountains, Papua, Indonesia. Reinwardtia 17(2): 133‒154. ‒‒ A study on structure and composition of the pristine montane forest previously untouched by human activities was conducted at the Foja Mountains in November 2008. We established a one-hectare plot divided into 100 subplots of 10 m × 10 m each. We enumerated all trees with DBH ≥ 10 cm which diameters were measured, heights were estimated and habitats were noted. We recorded 59 species, 42 genera and 27 families, comprising 693 trees with the total basal area (BA) of 41.35 m2/ha. The forest had lower species richness compared to those of lowland forests in Kalimantan, and Sumatra and montane forests in West Java. The Shannon-Wiener’s diversity index was 3.22. Nothofagus rubra (Importance Value, IV=47.89%) and Parinari corymbosa (IV=40.3%) were the dominant species, constituting the basis for designating the forest as the Nothofagus rubra - Parinari corymbosa association. To date, the dominance of N. rubra is unique to the Foja Mountains, as elsewhere in Papua the montane forests were dominated by N. pullei or other species. The species-area curve indicated a minimal area of 5000 m2. On the family level Fagaceae (IV=53.23%), Chrysobalanaceae (IV=40.53%) and Myristicaceae (IV=26.43%) were dominant. Verti-cally the forest consisted of four strata (A–D). In each stratum Nothofagus rubra, Platea latifolia, Parinari corymbosa and Myristica hollrungii were dominant. The diameter class distribution of Nothofagus rubra, Parinari corymbosa and Platea latifolia led us to assume that these species were regenerating well.